TRAUMA, GUILT, AND THE SILENT SELF: A PSYCHOANALYTIC READING OF CHIMAMANDA NGOZI ADICHIE’S PURPLE HIBISCUS - Sackaria, J Maria Prabina; Grace, Alby (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines Purple Hibiscus through a psychoanalytic lens, focusing on Kambili and Jaja’s psychological development under the authoritarian and abusive influence of their father, Eugene. Eugene's religious extremism has influenced the life of the children Kambili and Jaja. The children struggle to survive their father’s strict rules throughout their childhood. Applying Freudian and Lacanian theories, the study explores themes of repression, trauma, guilt, and the fragmented self. Kambili and Jaja’s silence, anxiety, and eventual awakening are examined as psychological responses to familial and ideological control. Not only the children but also the mother struggled in the hands of the tyrannic father. Mama’s passive submission is interpreted as neurotic behaviours shaped by repression and internalized fear.